Vouchers for Private Schooling in Colombia: Evidence from a Randomized Natural Experiment - Angrist, Joshua; Bettinger, Eric; Bloom, Erik; King, Elizabeth; Kremer, Michael (American Economic Review, 2002)
Colombia used lotteries to distribute vouchers which partially covered the cost of private secondary school for students who maintained satisfactory academic progress. Three years after the lotteries, winners were about 10 percentage points more likely to have finished 8th grade, primarily because they were less likely to repeat grades, and scored 0.2 standard deviations higher on achievement tests. There is some evidence that winners worked less than losers and were less likely to marry or cohabit as teenagers. Benefits to participants likely exceeded the $24 per winner additional cost to the government of supplying vouchers instead of public-school places.